Eksplorasi Antibakteri dari Kapang Tanah Arboretum - Rizal Dwinto Rochman; Titiek Sunartatie; Usamah Afiff (Institut Pertanian Bogor, 2020)
Research to discover new antibacterial agent has been increasing due to the increasing number of pathogenic bacteria become antibiotic-resistant. Microbiomes in soil mold have antibacterial potency by producing secondary metabolites. The aim of this research was to isolate soil molds from the Faculty of Forestry Arboretum at IPB University. Arboretum’s soil was sampled ± 7.5 g from several points with maximum depth of 15 cm from surface. Mold isolate were cultivated for 28 days using waterbath shaker. Cultivated mycelium and soil filtrate were then separated and extracted using different methods and solvents, prior to antibacterial activity test using agar well diffusion method. Six isolates from Aspergillus, Penicillium, Paecilomyces, and Verticilium were used in this research. Cultivatation using sabouraud dextrose broth (SDB) contains pepton and dextrose in 25°C capable of stimulating mold growth. The research showed the result of secondary metabolit had antibacterial characteristic toward tested bacteria. The results of antibacterial activity test on both mycelium and soil filtrate extract showed that soil mold isolates had antibacterial activity against Staphylococcus aureus and Escherichia coli. Isolate 103A originated from soil filtrate formed the largest inhibition zone on both tested pathogens. Keywords: antibacteria, mycelium, soil filtrate, soil mold